A1_6 Critical Pressure Inside the Large Hadron Collider - Longman, William Hunt Alexander; Turnpenney, Sam; Garreffa, Maria; Flatt, Kieran (Physics Special Topics, 2014)
<!–StartFragment–>In the paper we examine the vacuum conditions inside the beam pipe at the Large Hadron Collider. A hypothetical degradation of the ultra-high vacuum by air particles is modelled. By considering the mean free path, we calculate the maximum pressure that would allow the accelerated protons to complete one lap of the accelerator without being scattered by gas particles. This threshold pressure is found to be 0.246 mbar.<!–EndFragment–>